Recommencement of Sport Leagues With Spectators at the Adelaide Oval During the COVID-19 Pandemic: Planning, Experience, and Impact of a Globally Unprecedented Approach - Chan, Joel Ern Zher; Lee, Angela; Lease, Chris; Spurrier, Nicola (Frontiers in Public Health, 2021)
Non-pharmaceutical interventions including physical distancing and restriction on public gatherings were the cornerstone in controlling the COVID-19 pandemic, in the absence of effective vaccines and available treatment options. Many sport mega-events and sport leagues were cancelled or indefinitely postponed, leaving stadiums globally empty or converted to be used as part of the COVID-19 response. There were calls for exit strategies to be developed. With the early containment of COVID-19 in South Australia, various restrictions were lifted in a staged and controlled manner, including the reopening of the Adelaide Oval for recommencement of sport leagues with spectator attendance. This involved the collaboration between public health authorities, other governmental agencies, Adelaide Oval Stadium Management Authority, various sporting leagues etc. Recommencement of sport leagues with staged increase in number of attending spectators allowed various measures to be introduced, revisited and implemented accordingly, demonstrating that a case-by-case risk assessment can be conducted for mega-events during COVID-19, accounting for the epidemiological context at the time. Economic impacts and non-economic benefits of this recommencement were documented. This globally unprecedented, staged and controlled approach in returning spectators to sporting events during the COVID-19 pandemic could inform the reopening strategy of stadiums, recommencement of sport leagues and mega-events all over the world before herd immunity is achieved or in the event of future outbreaks.